2019
DOI: 10.1103/physrevd.100.024028
|View full text |Cite
|
Sign up to set email alerts
|

Black hole shadow in a general rotating spacetime obtained through Newman-Janis algorithm

Abstract: The Newman-Janis (NJ) algorithm has been extensively used in the literature to generate rotating black hole solutions from nonrotating seed spacetimes. In this work, we show, using various constants of motion, that the null geodesic equations in an arbitrary stationary and axially symmetric rotating spacetime obtained through the NJ algorithm can be separated completely, provided that the algorithm is applied successfully without any inconsistency.Using the separated null geodesic equations, we then obtain an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 103 publications
(97 reference statements)
1
101
0
Order By: Relevance
“…This metric is featured by the existence of the Carter constant of motion, which implies the separability of the Hamilton-Jacobi equation and null geodesic equations [4]. As we have mentioned previously, the NJA metric (19) also allows for separable null geodesic equations [25]. In addition, the Hamilton-Jacobi equation of the NJA metric is separable when H(r, θ) is an additively separable function.…”
Section: The Johannsen Parametrized Spacetimementioning
confidence: 88%
See 2 more Smart Citations
“…This metric is featured by the existence of the Carter constant of motion, which implies the separability of the Hamilton-Jacobi equation and null geodesic equations [4]. As we have mentioned previously, the NJA metric (19) also allows for separable null geodesic equations [25]. In addition, the Hamilton-Jacobi equation of the NJA metric is separable when H(r, θ) is an additively separable function.…”
Section: The Johannsen Parametrized Spacetimementioning
confidence: 88%
“…In Ref. [25], it has been shown that the general spacetime (19) allows for the separability of the null geodesic equations. However, this does not imply that the Hamilton-Jacobi equation is also separable.…”
Section: The General Newman-janis Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…2X (r ph ) X(r ph ) − aξ − ∆ (r ph ) η + (ξ − a) 2 = 0. (63) If we eliminate η and solve for ξ evaluated at r = r ph , it follows [74]…”
Section: Separation Of Null Geodesic Equations and Black Hole Shadowmentioning
confidence: 99%
“…First, we construct a rotating geometry and then obtain matter field satisfying the Einstein equations. For the first step, we employ the Newman-Janis (NJ) algorithm [17,18,19], which has become popular to study the rotational geometry [20,21,22,23,24,25]. This algorithm generates a rotating geometry from a known static one.…”
Section: Introductionmentioning
confidence: 99%